PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN (SURVEI PELANGGAN KARTU PRABAYAR IM3 PADA MAHASISWA KOTA LUBUKLINGGAU) - Hardi Mulyono (LPPM UNIVERSITAS BINA INSAN, 2016)
Indosat Multimedia Mobile (IM3) continues to develop according to the needs of its customers, especially young people. Customers want more service, they want a prepaid card that can meet their expectations and desires with a greater level of mobility and can explore in many cities. IM3 fulfills this and has proven to have a very broad national and international reach, reaching more than 132 countries in various parts of the world. This research is a quantitative research with a survey approach that seeks to find out how the effect of product quality on the satisfaction of IM3 prepaid card customers. Data collection techniques are by questionnaire, interview and documentation. For testing the instrument using the Validity, and Reliability test. While for data analysis techniques using multiple linear regression methods because the variables used are more than two variables, with the F test and t test. The results showed that Performance (X1), Features (X2), Reliability (X3), Conformance to Specifications (X4), and Service (X5) variables simultaneously had a significant effect on IM3 prepaid card customer satisfaction (Y). From the calculation of the F test obtained F count 12.28> F Table 2.30 with a p value of 0.000≤ 0.05. In addition, the value of Adjusted R Square which is equal to 0.350, which means the magnitude of the influence of independent variables on the dependent variable is 35%. And t test is known that partially Features, Conformity with Specifications and Services have a significant effect on the dependent variable while Performance and Reliability does not significantly influence the calculation of t count performance (X1) of 0.158 <t table 1.980, Feature (X2) has t count 2,019> t table 1,980, Reliability (X3) has t count 1,609 <t table 1,980, Conformity with Specifications (X4) has t count 3,004> t table 1,980 and Service (X5). the most dominant variable is the message source variable (X4) having t count 3.711> t table 1.980. while the most dominant variable is the Conformance with Specifications (X4) variable of 23.32%, the service variable (X5) is 17.80%, the feature variable (X2) is 15.36%, the reliability variable (X3) is 12.81 % and performance variable (X1) of 2.52%